Depth structure of the Gorishne-Plavninsk structure and general principles of geological and geophysical study of the Krivoy Rog-Kremenchug iron-ore strip - В. А. Єнтин; М.І. Орлюк; О. І. Білоус; О.Б. Гінтов; В.Г. Малахов; В.Г. Бахмутов; І.О. Качан; М.І. Бакаржієва; І.Б. Макаренко; О.С. Савченко; Т.М. Самойленко; А.В. Марченко; et al. (Геофизический журнал, 2022)
The article presents the results of the newest research performed by the State Enterprise «Ukrainian Geological Company» and the Institute of Geophysics of the National Academy of Sciences of Ukraine in 2021 to find out the morphology and elements of occurrence of an redeposit within the limits of the Gorishne-Plavninsk-Lavrikovsk area of the Krivoy Rog-Kremenchug iron-ore strip. In the process of geological and geophysical studies, a large body of new geological and geophysical data was obtained regarding the deep structural and morphological features of the construction of the Gorishne-Plavninsk structure (GPS), associated with the Krivoy-Rog deep fracture zone.